Analysis of a Dynamic Response of the Cochlea Using Fluid-Structure Interaction Model - Konrad KAMIENIECKI; Janusz PIECHNA; Paweł BORKOWSKI (Engineering Transactions)
A one-dimensional (1D) model of the cochlea of the inner ear has been built and validated against the previously built three-dimensional (3D) fluid-structure interaction (FSI) model of the cochlea. The 1D model has been used to assess the influence of the round window impedance on the pressure distribution in the cochlea. It was shown that high impedance, which enables compression reflection pressure wave at the round window, leads to the biggest pressure difference between the scala vestibule and the scala tympani in the cochlea, which may lead to a stronger excitation of the basilar membrane.